UMP campus successfully disinfected and welcomes its workforce - UMP, PNC (2020)
As a precautionary measure to combat the spread of the Covid-19 outbreak, Universiti Malaysia Pahang (UMP) carried out sanitation operations at several focus areas and buildings at both UMP campuses in Gambang and Pekan from March 23 to April 7, 2020.